Hubungan Modal Sosial dan Perencanaan - Masik, Agustomi (Journal of Regional and City Planning, 2005)
The  metadicipline  nature  of  planning  often  misleads  students  relating  to what is the focus of this field. Questions arise whether a planner should be focusing  on  physical  aspects  or should  also  dealing  with  wider  concern including social and economic aspe cts. This article explores the meaning of planning,  and  assess  role  of  social  aspect  in  planning  especially  social capital  concept.  It  reveals that  planning  and  social  capital are  reciprocal. Applying  interactive  and  collaborative  planning  approaches  based   on communicative  rationality  increase  social  capital  stock.  Conversely,  social capital  has  also   importan t  roles  in  planning  which  are   supporting   for sustainable  development,  contextualizing  framework,  and  guid ing  the direction of  social change, and bridg ing dialogue among disciplines.Keywords: social capital, planning theory, planning